The new grounds for cassation in labour matters - Bonilla Del Castillo, Jorge Luis (2023)
This article analyzes the amendments to the appeal in labor matters, incorporated by Law No. 31699, a rule that was promulgated on February 14, 2023 and published in the newspaper El Peruano on March 1 of the same year. The objective is to determine how much they contribute to the desired optimization of this resource and the fulfillment of its purposes, for which we focus our attention particularly on its new causes. To this end, we will address some topics of the drafting of the Labor Procedure Law (Law No. 26636), the repealed wording of the New Labor Procedure Law (Law No. 29497), the explanatory memorandum contained in Bill No. 930/2021-PJ, and the respective opinions issued by the Labor and Social Security Commission and the Justice and Human Rights Commission of the Congress of the Republic of the Peru.